The Role of Interaction, Entertainment, and Customization in Increasing Brand Engagement and Brand Loyalty of Skintific Students on TikTok - Intan Melinda; Rahmad Solling Hamid; Edi Maszudi (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study aims to analyze the influence of interaction, entertainment, and customization on Skintific's brand engagement and loyalty on the TikTok platform. In the digital era, social media has become a crucial tool in marketing strategies, enabling companies to connect directly with consumers. The method used was quantitative, with data collected through questionnaires from 240 university students in Palopo City. The analysis results show that interaction has a positive and significant influence on brand engagement. Furthermore, entertainment content has been shown to be effective in enhancing consumer experience, while product customization contributes to increased consumer loyalty. These findings provide valuable insights for Skintific and other marketers to design more effective digital marketing strategies, thereby increasing consumer engagement and loyalty in a competitive market.